Kinds of figurative language in three songs of Disney movies original soundtrack - Sari, Wati Purnama (LADU: Journal of Languages and Education, 2021)
Background: Figurative language are quite popular in songâ€™s lyric because we can hide our messages or what we had experienced or felt. That became a reason why we should learn more about kinds of figurative language in order to understand more about the real meanings that are conveyed in the songs.Purpose: The aim for this research is to discover the kinds of figurative language in three songs of Disney Movies Original Soundtrack.Design and methods: In this research, the researcher used qualitative methods. In analyzing the data, the researcher used Mezoâ€™s theory of figurative language. The source of data for this research are from Disney movies original soundtrack namely, the song entitled â€œLead the wayâ€ from Raya and the last dragon movie, â€œLove, brave and trueâ€ from Mulan movie and â€œHow does a moment last foreverâ€ from the Beauty and the Beast movie. The data from this research are the sentences that had figurative language.Â Result: After doing an analysis, there are 21 data appeared. The researcher discovered 6 kinds of figurative language from those data namely, Hyperbole (6 data), Metaphor (5 data), Personification (4 data), Litotes (2 data), Simile (2 data), and Synecdoche (2 data).